2017
DOI: 10.1177/1054773817714562
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Coping Strategies Influencing the Quality of Life in Patients With Brain Tumor

Abstract: The study purpose was to evaluate how much of the variance in quality of life (QOL) among Taiwanese patients with brain tumor could be accounted for by resilience and coping strategy. This cross-sectional study included 95 patients who had undergone a treatment of operations or chemotherapy or radiotherapy relevant to brain tumor after at least 1 month and completed the European Organization for Research and Treatment of Cancer QOL Questionnaire-Brain Cancer Module (EORTC QLQ-BN20), Resilience Scale (RS), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
9
27
1
Order By: Relevance
“…The nding that resilience, PSS, and CS (i.e., confrontation and resignation) had signi cant in uences on HRQoL is consistent with previous research [43][44][45], and partially supports our rst hypothesis that psychosocial factors are independent predictors of HRQoL. However, the avoidance CS did not signi cantly in uence HRQoL.…”
Section: Discussionsupporting
confidence: 90%
“…The nding that resilience, PSS, and CS (i.e., confrontation and resignation) had signi cant in uences on HRQoL is consistent with previous research [43][44][45], and partially supports our rst hypothesis that psychosocial factors are independent predictors of HRQoL. However, the avoidance CS did not signi cantly in uence HRQoL.…”
Section: Discussionsupporting
confidence: 90%
“…The nding that resilience, PSS, and CS (i.e., confrontation and resignation) had signi cant in uences on HRQoL is consistent with previous research [44][45][46], and partially supports our rst hypothesis that psychosocial factors are independent predictors of HRQoL. However, the avoidance CS did not signi cantly in uence HRQoL.…”
Section: Discussionsupporting
confidence: 90%
“…To evaluate the physical ability of patients, the Karnofsky Performance Status scale (KPS) was employed, with scores ranging from 0 (dead) to 100 (normal) [20]. Details of the sample in this study have been reported elsewhere [21,22]. For the purposes of this article, data obtained using the following instruments were analyzed.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%